2020
DOI: 10.1016/j.cjtee.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of calorie and protein intake among acute and sub-acute traumatic brain injury patients

Abstract: Purpose Malnutrition is a common problem among hospitalized patients, especially among traumatic brain injury (TBI) patients. It is developed from hypermetabolism and the condition may worsen under the circumstance of underfeeding or incompatible dietary management. However, the data of nutrient intake especially calorie and protein among TBI patients were scarce. Hence, this study aimed to determine the calorie and protein intake among acute and sub-acute TBI patients receiving medical nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In the 1980s, researchers revealed that the physiological characteristics of severe TBI patients in the acute phase were large amounts of catabolism, increased energy expenditure, severe pro-inflammatory reactions, insulin resistance, and increased AGI (acute gastrointestinal injury) risk. Some studies have unilaterally emphasized the need to provide enough calories for patients with severe TBI 8 while the appearance of insulin resistance, gastrointestinal dysfunction, hyperglycemia on the nervous system, and other sequelae was caused by the lack of evaluation. 9 After entering the ICU, patients with severe brain injury will be given corresponding treatments such as hypothermia, sedation, and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, researchers revealed that the physiological characteristics of severe TBI patients in the acute phase were large amounts of catabolism, increased energy expenditure, severe pro-inflammatory reactions, insulin resistance, and increased AGI (acute gastrointestinal injury) risk. Some studies have unilaterally emphasized the need to provide enough calories for patients with severe TBI 8 while the appearance of insulin resistance, gastrointestinal dysfunction, hyperglycemia on the nervous system, and other sequelae was caused by the lack of evaluation. 9 After entering the ICU, patients with severe brain injury will be given corresponding treatments such as hypothermia, sedation, and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A study among patients with mild to moderate TBI (according to the Glasgow scale) showed that a significant number of patients had reduced protein levels at the start of hospitalisation, which gradually improved after nutritional treatment (on the first day of nutritional treatment, protein levels increased by 23.1%, while 75% of the total protein requirement was reached on the day of discharge). The authors of the study believe that optimal nutrient intake, especially calories and protein, is crucial to ensure an optimal recovery process, as well as minimising the risk of infection and complications [25]. A study by Stewart et al among critically ill patients revealed that calorie and protein deficits in patients with moderate to severe TBI (Glasgow score 9-12 and 3-8, respectively), reached 18,242 kcal (1 kcal = 4186 kJ) and 1315 g protein, respectively [26].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a common problem among hospitalized patients, especially among patients with TBI. It develops as a result of hypermetabolism, and the condition can worsen with undernourishment or poor dietary management [24,25]. In particular, elderly trauma patients and patients with postoperative infections should be carefully monitored during hospitalisation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Abdullah et al (57) conducted an observational intervention looking at the calorie and macronutrient intakes of patients hospitalized after sustaining a TBI. In order to prevent underfeeding and unsuited dietary management practices, researchers wanted to determine an accurate nutritional baseline requirements to support patients during their length of stay at hospital and recovery post TBI.…”
Section: Acute Caloric and Macronutrient Intake Post Mtbimentioning
confidence: 99%